Pelatihan Membaca Al Qur’an dengan Ilmu Tajwid Metode Tahsin Tilawah untuk Meningkatkan Kualitas Bacaan Bagi Remaja Masjid di Desa Gedangan - Agus Salim Marpaung; Putri Suaidah Pulungan (MADANI PUBLISHER INDONESIA, 2025)
Training to read the Al-Qur'an with tajwid using the Tahsin Tilawah method aims to improve the quality of Al-Qur'an reading for mosque teenagers in Gedangan Village. This activity is motivated by the importance of the ability to read the Koran correctly according to the rules of tajwid, which is still a challenge for most teenagers in the village. The Tahsin Tilawah method was chosen because of its systematic and effective approach in correcting reading errors, as well as providing a deeper understanding of the laws of recitation. This training was carried out in several stages, namely a pre-test to determine the participants' initial abilities, an intensive training session covering the theory and practice of recitation, and a post-test to measure the improvement in reading quality. The results of the training showed a significant increase in the ability to read the Al-Qur'an with correct recitation. Mosque teenagers who took part in this training experienced improvements in letter articulation, application of reading laws, and increased self-confidence in reciting verses from the Koran. It is hoped that this training can become a sustainable program to produce young people who are not only fluent in reading the Koran, but also understand the rules of recitation well.